Evidentialism about Faith and the Justification Encroachment Dilemma. Issue 1 (2nd January 2021) - Gillham, Alex R
ABSTRACT: In this paper, I develop what I call the Justification Encroachment (JE) Dilemma for Dormandy's Evidentialism about Faith (EaF). The dilemma is this. If JE is true, then belief about objects of faith will be very difficult to justify, perhaps even impossible. If JE is false, then beliefs about objects of faith require no greater justification than any other belief, so that faith requires no more respect for evidence than anything else. After developing each horn, I consider very briefly how a proponent of EaF might respond.